The aging rhesus macaque as a potential model for Alzheimer's disease/dementia: An in vivo study of [11C]PIB, [11C]UCB‐j, [18F]MK‐6240 and working memory performance: Development of new models and analysis methods/validation of pre‐clinical methods. (7th December 2020) - Fang, Xiaotian T.; Williams, Graham; Castner, Stacy; Holden, Daniel; Zheng, Ming‐Qiang; Najafzadeh, Soheila; Ropchan, Jim R.; Arnsten, Amy F.T.; Horvath, Tamas; Carson, Richard E.
Abstract: Background: Nonhuman primates (NHPs) exhibit age‐related cognitive impairments, synaptic loss, and accumulation of tau and amyloid in dorsolateral prefrontal cortex (dlPFC) and entorhinal cortex (ERC). In a cohort of NHPs with longitudinal cognitive data, we perform SV2A ([ 11 C]UCB‐J), amyloid ([ 11 C]PIB), and tau ([ 18 F]MK‐6240) PET. We aim to 1) investigate in vivo relationships and age‐related change in amyloid, tau, and synaptic density (SV2A) and 2) to relate these to cognition in NHPs. Method: Middle‐aged (n = 5, 10.4 ± 0.5 y.o.) and old (n = 17, 19.9 ± 2.7 y.o.) NHPs were dynamically PET scanned (FOCUS 220) following i.v . injection of each of [ 18 F]MK‐6240 (173 ± 12 MBq), [ 11 C]PIB (131 ± 52 MBq), and [ 11 C]UCB‐J (105 ± 34 MBq). Structural MR scans were acquired for registering PET to template space. Outcome measures were SUVR40‐60 for [ 11 C]PIB, SRTM2‐derived DVR for [ 11 C]UCB‐J, and SUVR90‐110 for [ 18 F]MK‐6240. Cerebellum was used as reference ([ 11 C]PIB, [ 11 C]UCB‐J), and cerebellar gray matter for [ 18 F]MK‐6240. A subset of the old NHPs (n = 15) were tested with the spatial‐delayed response task to assess working memory performance. Outcome measures: number‐of‐wells, time‐delay, and combined score (number‐of‐wells × time‐delay); higher score indicates better memory performance. Result: No regional mean differences were observed in amyloid or SV2A between middle‐aged and old NHPs, though old NHPs exhibited higher variance for all tracers; mean tau was elevated in dlPFC ( p  = 0.0031) and hippocampus (HC, p  = 0.011) in old NHP compared with middle‐aged (Figure 1). In ERC, a positive relationship was found between tau and amyloid), and in HC, a negative correlation was found between tau and SV2A (Figure 2A). Synaptic density displayed a positive relationship with combined score both in dlPFC ( p  = 0.0055, R 2  = 0.46) and HC ( p  = 0.029, R 2  = 0.32) (Figure 2B). Tau had a negative relationship with number‐of‐wells in dlPFC ( p  = 0.05, R 2  = 0.40), and combined score in HC ( p  = 0.015, R 2  = 0.40). Conclusion: NHPs exhibit age‐related changes in canonical AD biomarkers as seen by PET. PET markers of SV2A, tau, and amyloid in known early‐pathology regions (dlPFC, HC) correlate appropriately with working memory performance. These studies demonstrate the potential of NHPs as a highly useful model for human AD.